2016
DOI: 10.17645/up.v1i2.609
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Cultural Ecosystem Services through Instagram Images: The Potential of Social Media Volunteered Geographic Information for Urban Green Infrastructure Planning and Governance

Abstract: With the prevalence of smartphones, new ways of engaging citizens and stakeholders in urban planning and governance are emerging. The technologies in smartphones allow citizens to act as sensors of their environment, producing and sharing rich spatial data useful for new types of collaborative governance set-ups. Data derived from Volunteered Geographic Information (VGI) can support accessible, transparent, democratic, inclusive, and locally-based governance situations of interest to planners, citizens, politi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 34 publications
1
87
0
Order By: Relevance
“…This has included preferences for biodiversity extracted from Instagram and Flickr, where Hausmann et al (2017) found no significant difference compared to traditional surveys. The spatial distributions of images from Instagram for the City of Copenhagen have been found to show the main hotspots (Guerrero et al, 2016). Image feature extraction on crowd-sourced data using a neural network has been used to ascertain outdoor elements that are found to be scenic (Seresinhe, Preis and Moat, 2017) and the use of geo-tagged photos from Flickr have been used in multiple studies as a proxy for visitation.…”
Section: Introductionmentioning
confidence: 99%
“…This has included preferences for biodiversity extracted from Instagram and Flickr, where Hausmann et al (2017) found no significant difference compared to traditional surveys. The spatial distributions of images from Instagram for the City of Copenhagen have been found to show the main hotspots (Guerrero et al, 2016). Image feature extraction on crowd-sourced data using a neural network has been used to ascertain outdoor elements that are found to be scenic (Seresinhe, Preis and Moat, 2017) and the use of geo-tagged photos from Flickr have been used in multiple studies as a proxy for visitation.…”
Section: Introductionmentioning
confidence: 99%
“…New methods are being developed and combined to measure social place values, such as GPS tracking and linguistic approaches (Gosal et al 2018; Wartmann and Purves 2018) as well as social media volunteered geographic information (e.g. analyses of shared images and tags from social media activities) (Jenkins et al 2016;Guerrero et al 2016). Such applications, in spite of their specific methodological limitations (e.g.…”
Section: Limitations and Recommendations For Further Researchmentioning
confidence: 99%
“…Indeed, georeferenced images have been used as proxies of landscape preference at both regional (Tenerelli et al 2016, Yoshimura andHiura 2017) and continental scales (van Zanten et al 2016). The potential value of image descriptions has also been recognized in exploring landscapes (Dunkel 2015) and extracting information related to cultural ES (Richards and Friess 2015, Guerrero et al 2016, Figueroa-Alfaro and Tang 2017, Oteros-Rozas et al 2017. User-generated content can at least start to bridge the data gap between expert and bottom-up perceptions of landscape, and provide more spatially extensive data, at lower costs.…”
Section: Challenges In Landscape Characterizationmentioning
confidence: 99%